Regular lexical polysemy and facets in the lexicography of Spanish - Rojas Gallardo, Darío (Boletín de Filología, 2011)
In this paper we analyse the treatment of regular lexical polysemy and facets from a metalexicographic perspective in a sample of eight monolingual, general-purpose and semasiological dictionaries of Spanish. We analyse 82 nouns, belonging to general Spanish, which present the semantic phenomena in question, as they appear in 656 lexicographical articles. Our main goal is to set foundations for the elaboration of a lexicographical treatment that synthesizes the good practices of the Hispanic lexicographical tradition and, at the same time, overcomes its problems. Our investigation reveals that these dictionaries show, to a larger or smaller extent, considerable defects in the treatment of lexical units showing regular lexical  polysemy or facets. We propose that these defects can be rectified through five specific principles for the treatment of these kinds of lexical units.